Evaluation of radiologic predisposing factors for greater trochanteric pain syndrome - Şahin, Erdem; Tanrıöver, Altuğ (The European Research Journal, 2023)
Objectives: Greater trochanteric pain syndrome (GTPS) is one of the causes of lateral hip pain. We aimed to determine the significance of certain anatomical parameters related to GTPS in imaging tests. Methods: Data of patients who were treated with glucocorticoid injection for trochanteric bursitis in our clinic between July 2019 and July 2022 for GTPS were analyzed. The control group was constituted of patients without GTPS but with hip and spinal problems who had pelvic computerized tomography (CT) images and undergone robotic-assisted knee arthroplasty. Standard anteroposterior pelvic radiograms, pelvic CTs, or magnetic resonance images were evaluated for anatomical parameters. Results: Among anatomical parameters, acetabular anteversion, length of trochanter major, and abductor index were significantly different between the patients with and without GTPS. Although mean age was different between the GTPS and control patient groups, age was not found to be correlated with any anatomical parameter. Abductor lever arm length (p = 0.001) and abductor index (p = 0.009) were found to be correlated. Conclusions: The length of trochanter major and abductor index were shown to be predisposing anatomical parameters for GTPS.